Python gmail dictionary attack using wordlist - Widianto, Septian Rheno; Maulana, Muhammad Sony; Pratama, Eri Bayu; Firmansyah, Yoki; Nurmalasari (AIP conference proceedings, 2023)
Dictionary attack is a very effective attack to crack the code and is often used by hackers to break into passwords, such as email accounts, social networking accounts, website administrator pages, and others. Dictionary attack is considered effective because it utilizes human psychology, namely the habit that account users will use easy-to-remember words as passwords for a particular account. In addition, dictionary attacks have also been developed for variations as well as effectiveness, so that until now this technique is still often used to break user passwords for an account. In the context of cryptanalysis and computer security, dictionary attack is a technique against ciphers or against authentication mechanisms by determining the decryption key by looking for possible combinations of words contained in a dictionary. Dictionary attack is also a development of brute force attack, which is trying to crack the code by trying one by one possibility repeatedly (exhaustive search). A dictionary attack is not trying to combine the available characters one by one like brute force, but rather trying the most successful word combination by inputting a defined "list of words" (also known as a dictionary), which usually comes from a list of common word combinations. contained in a dictionary, such as an English dictionary. In this study using the ptyhon programming language for scripting, utilizing smtp.gmail.com with port 465 and with 1,406,537 wordlist passwords, then testing using the Backbox Linux platform, getting 100% accurate results for gmail passwords.